1987
DOI: 10.1002/ajh.2830240303
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of inhibitors in patients with severe and moderate hemophilia a treated with factor VIII concentrates

Abstract: Recent data published on the prevalence of inhibitors to factor VIII in hemophiliacs on treatment show great variations, with prevalence rates ranging from 3.6 to 14.2%. We have studied the cumulative risk of inhibitor development in a cohort of 62 patients with hemophilia A. All patients were born after 1960, were natives of the Vienna area, had a factor VIII activity of less than 5%, and were treated at least once. Using the method of Cutler and Ederer, the cumulative risk of inhibitor development was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 7 publications
3
47
1
Order By: Relevance
“…The figure illustrates the maximum inhibition obtained using 30 g/ml human antibodies. Plasma samples were obtained before (1) and at different times (2 to 5) during desensitization by FVIII infusions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The figure illustrates the maximum inhibition obtained using 30 g/ml human antibodies. Plasma samples were obtained before (1) and at different times (2 to 5) during desensitization by FVIII infusions.…”
Section: Resultsmentioning
confidence: 99%
“…More than 20% of hemophilia A patients under Factor VIII (FVIII) 1 infusion therapy develop an antibody response toward FVIII (1,2). These antibodies, also called FVIII inhibitors, are routinely detected by the Bethesda method, an assay system carried out in plasma and in which the capacity of antibodies to neutralize the procoagulant activity of FVIII is measured (3).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature it has been reported that inhibitors mostly develop before the age of 20, and the cumulative risk of developing an inhibitor at age 25 is 24% [17, 31]. The age at which the inhibitors were first detected ranged from 1 month to 5.2 years in one study, whereas it ranged from 3 to 7 years in another study [11, 17]. Colvin et al [29]found that 38% of the patients who developed an inhibitor were older than 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…In studies using recombinant F VIII concentrates, inhibitors formed in 19–24% of previously untransfused patients with severe hemophilia [6, 7, 13], and in studies using monoclonally purified plasma-derived concentrates, inhibitors developed in 6–18% [14, 15]. It has been shown that one third of the inhibitors will develop by age 4 years and more than 50% will develop by age 9 years [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…Former studies mostly considered the prevalence of inhibitor development, thus underestimating its true risk. Prevalence ranged between 7 and 18% [3, 4, 7, 9, 10]. …”
Section: Introductionmentioning
confidence: 99%